PENGARUH DISIPLIN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT SELARAS INDO SAKTI - Hadi, Fakhrul; Novita, Dina (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of discipline and physical work environment on employee performance at PT Selaras Indo Sakti. The method used is descriptive quantitative. Data analysis includes validity tests, reliability tests, classical assumption tests, descriptive analysis, simple regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results indicate that discipline has a positive effect on employee performance, with the equation Y = 17.271 + 0.627 X1. The correlation coefficient is 0.709, showing a strong relationship between the two variables. The coefficient of determination, or the contribution of the effect, is 0.502 or 50.2%, with the remaining 49.8% influenced by other factors. Hypothesis testing shows that the calculated t-value is greater than the t-table value (7.100 > 2.009). Thus, H0 is rejected and Ha is accepted, indicating a significant positive effect of X1 on Y. The physical work environment also has a positive effect on employee performance, with the equation Y = 7.137 + 0.811 X2. The correlation coefficient is 0.858, indicating a strong relationship. The coefficient of determination is 0.737 or 73.7%, with the remaining 26.3% influenced by other factors. Hypothesis testing reveals that the calculated t-value is greater than the t-table value (11.835 > 2.009). Therefore, H0 is rejected and Ha is accepted, signifying a significant effect of X2 on Y. Discipline and physical work environment both have an impact on employee performance, with the combined equation Y= 6.168 + 0.158 X1 + 0.688 X2. The correlation coefficient is 0.867, which indicates a very strong relationship. The coefficient of determination, when considered simultaneously, is 0.752 or 75.2%, with the remaining 24.8% influenced by other factors. Hypothesis testing shows that the calculated F-value is greater than the F-table value (74.314 > 3.187). Therefore, H0 is rejected and Ha is accepted, demonstrating a significant simultaneous effect of X1 and X2 on Y.